PENGARUH ARUS TERHADAP KEKERASAN HASIL PENGELASAN BAJA ST 60 MENGGUNAKAN PENGELASAN SMAW - Ma'ruf Ma’ruf (INFO-TEKNIK, 2013)
The purpose of this study was to determine the effect of the current violence SMAW welds on weld metal, HAZ and base metal regions ST 60 steel using E6013 electrodes. This study uses eksprimental, hardness testing was conducted using the Rockwell B (HRB). Hardness testing with penetrator ball Ø 1/16 "with a 981 N load suppression (100 Kgf). Conclusion is that large currents affect the hardness of steel ST 60 welds using SMAW welding. Hardness of weld metal at the highest current 90 A, the area the highest hardness in the HAZ 90 A current and highest hardness of the parent metal in the current 70 A.